Social Support and Quality of Life in Elderly People Who Have Been Left Behind by Their Life Partners in Bitung - Dwisetyo, Bayu; Dewi, Yunita F.A (Jurnal Keperawatan Profesional (KEPO), 2025)
Older adults are frequently misunderstood and perceived negatively by the public, with the assumption that they are a burden to their families and the wider community. This study aimed to examine the relationship between social support and quality of life among older adults who have lost their spouses in Kadoodan Village, Bitung City. A quantitative research method was applied using an analytical observational design with a cross-sectional approach. A total of seventy-three older adults who met the inclusion criteria were selected through purposive sampling. The instruments used in this study included the Interpersonal Support Evaluation List (ISEL) to assess social support and the WHOQOL-BREF questionnaire to measure quality of life. The findings showed that older adults with good social support and good quality of life constituted the largest proportion, namely forty-six subjects (36%). Meanwhile, only two subjects (2,7%) demonstrated good social support but poor quality of life. The Chi-square test yielded a p-value of <0,001, indicating a statistically significant association between social support and quality of life. The study concluded that social support plays an important role in improving the quality of life of older adults who have lost their spouses. It is recommended that families, communities, and healthcare providers become more actively engaged in providing sustained attention, interaction, and support for older adults.